The Influence of Perceived Value, Brand Image and Celebrity Endorsement on Customer Loyalty of Local Futsal Shoes - Aly, Baharuddin; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of perceived value, brand image, and celebrity endorsement on customer loyalty toward local futsal shoe brands in Malang City. Design/methodology/approach – This study employs an explanatory research design to test the relationships among perceived value, brand image, celebrity endorsement, and customer loyalty. Data were collected from 100 respondents aged at least 18 years, both male and female, who reside in Malang City and have purchased or used local futsal shoe brands such as Specs, Ortuseight, and Mills. A non-probability sampling method with purposive sampling technique was applied. Primary data were obtained through a Likert-scale questionnaire and analyzed using multiple linear regression. Findings – The results indicate that perceived value, brand image, and celebrity endorsement each have a positive and significant effect on customer loyalty. These findings suggest that higher perceived value, a strong brand image, and effective celebrity endorsements contribute to increased customer loyalty toward local futsal shoe brands. Originality/value – This study contributes to consumer behavior and sports footwear marketing literature by integrating perceived value, brand image, and celebrity endorsement as determinants of customer loyalty in the context of local Indonesian futsal shoe brands. The findings provide practical implications for companies in enhancing product quality, strengthening brand identity, and optimizing endorsement strategies to retain customers and reduce brand switching.